RC T beams strengthened to shear with carbon fiber composites - Spagnolo JR,L. A. (2013)
This paper presents the experimental data of the behavior of reinforced concrete beams strengthened to shear with carbon fiber composites. The tests were composed of eight T beams, b w=15 cm, h=40 cm, flange width 40 cm, flange height 8 cm, and length 300 cm, divided into two series with the same longitudinal steel reinforcement and a reference beam without strengthening in each series. The beams had two types of arrangement of internal steel stirrups. The test variables were the internal and external geometric ratio of the transverse reinforcement and the mechanical ratio of carbon fiber composites stirrups. All the beams were loaded at two points. The strengthened beams were submitted to a preloading and the strengthening was applied to the cracked beam. All the beams were designed in order to guarantee shear failure, and the ultimate load of the strengthened beams was 36% to 54% greater than the reference beams. The Cracking Sliding Model applied to the strengthened beams was evaluated and showed good agreement with the experimental results.